Genome-wide transcription landscape of citric acid producing Aspergillus niger in response to glucose gradient - Zheng, Xiaomei; Du, Peng; Gao, Kaiyue; Du, Yimou; Cairns, Timothy C.; Ni, Xiaomeng; Chen, Meiling; Zhao, Wei; Ma, Xinrong; Yang, Hongjiang; Zheng, Ping; Sun, Jibin (Frontiers in Bioengineering and Biotechnology, 2023)
Aspergillus niger is the main industrial workhorse for global citric acid production. This fungus has complex sensing and signaling pathways to respond to environmental nutrient fluctuations. As the preferred primary carbon source, glucose also acts as a critical signal to trigger intracellular bioprocesses. Currently, however, there is still a knowledge gap in systems-level understanding of metabolic and cellular responses to this vital carbon source. In this study, we determined genome-wide transcriptional changes of citric acid-producing A. niger in response to external glucose gradient. It demonstrated that external glucose fluctuation led to transcriptional reprogramming of many genes encoding proteins involved in fundamental cellular process, including ribosomal biogenesis, carbon transport and catabolism, glucose sensing and signaling. The major glucose catabolism repressor creA maintained a stable expression independent of external glucose, while creB and creD showed significant down-regulation and up-regulation by the glucose increase. Notably, several high-affinity glucose transporters encoding genes, including mstA, were greatly up-regulated when glucose was depleted, while the expression of low-affinity glucose transporter mstC was glucose-independent, which showed clear concordance with their protein levels detected by in situ fluorescence labeling assay. In addition, we also observed that the citric acid exporter cexA was observed to be transcriptionally regulated by glucose availability, which was correlated with extracellular citric acid secretion. These discoveries not only deepen our understanding of the transcriptional regulation of glucose but also shed new light on the adaptive evolutionary mechanism of citric acid production of A. niger.